Product sequencing: co-evolution of knowledge, capabilities and products - Helfat, Constance E.; Raubitschek, Ruth S. (Strategic Management Journal, 2000)
This article provides a conceptual model that explains how the coevolution of organizational knowledge, capabilities, and products over long time spans can result in competitive advantage through innovation and strategic linkage of products at a point in time and over time. At the heart of the model are sequences of products within and across markets, supported by an underlying system of knowledge and systems of learning. This dynamic model brings the importance of the products themselves, supported by vertical chains of activities, into the analysis of resource and knowledge-based competitive advantage. The model also suggests that we can think about the evolution of firms, and by implication the evolution of industries, not only in terms of knowledge and capabilities, but also in terms of vertical chains and products. Short company histories illustrate the workings of the model. Copyright © 2000 John Wiley & Sons, Ltd.